Analisis Komparatif Pengaruh PH dan Suhu Terhadap Aktivitas Enzim Berdasarkan Kajian Delapan Jurnal Biokimia Terkini - Alya Putri Wanda; Anisa Safitri; Alika Intan Shafila; Nazwa Zafira Azhari Nasution; Miftahul Khairani (INDO PUBLISHING, 2026)
Enzymes are biocatalysts that play an important role in various metabolic processes of living organisms. Enzyme activity is influenced by several environmental factors, especially pH and temperature. This article aims to analyze and compare the findings of eight recent biochemical journals discussing the effect of pH and temperature on enzyme activity. The method used in this study was a literature review by examining relevant scientific journals published in recent years. The results showed that each enzyme has different optimum pH and temperature conditions depending on the type of enzyme and its microbial source. Excessive temperature may cause enzyme denaturation, while unsuitable pH can alter the structure of the enzyme’s active site and reduce its catalytic activity. Based on the comparison of several studies, it can be concluded that pH and temperature are the main factors affecting enzyme stability and activity in biochemical reactions.